2012
DOI: 10.2166/wst.2012.802
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sediment quality and pore water ecotoxicity in Kebir Rhumel basin (NE-Algeria): a combined approach

Abstract: The objectives of this study are to use different approaches to assess the current pollution status in the wadis of the Kebir Rhumel basin. First, sediment trace metal contents were measured by flame atomic absorption spectroscopy. Then, sediment quality was assessed on the basis of contamination assessment indexes such as: Geoaccumulation Index (Igeo), Contamination factor (C(f)), Contamination degree (C(d)), Sediment Pollution Index (SPI) and SEQ guidelines (Consensus Sediment Quality Guidelines). In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This increase is probably mainly induced by intensive vehicle traffic and emissions of some industrial complexes related to urban and A c c e p t e d M a n u s c r i p t 5 industrial areas in the Rhumel subbasin. Sahli et al (2011) reported that the sediment quality of Rhumel Wadi in this part is medium to poor for the studied metals (Sahli et al 2012).…”
Section: Metal Contentsmentioning
confidence: 80%
See 1 more Smart Citation
“…This increase is probably mainly induced by intensive vehicle traffic and emissions of some industrial complexes related to urban and A c c e p t e d M a n u s c r i p t 5 industrial areas in the Rhumel subbasin. Sahli et al (2011) reported that the sediment quality of Rhumel Wadi in this part is medium to poor for the studied metals (Sahli et al 2012).…”
Section: Metal Contentsmentioning
confidence: 80%
“…In previous studies significant enrichment of metals in the Rhumel subbasin was observed. This included cases of lead enrichment in soils of wadi banks (Krika, Rached, and Du Laing 2013) and Cd, Co, Cr, Cu, Pb and Zn enrichment in water and sediment of this wadi (Afri-Mehennaoui, Sahli, and Mehennaoui 2004;Sahli et al 2011Sahli et al , 2012. The soil banks of Rhumel Wadi could be discharging appreciable quantities of wastes from urban and industrial areas.…”
Section: Introductionmentioning
confidence: 99%
“…This triggers questions like whether the Earth is capable of coping with such a burden of anthropogenically-released chemicals (Gavrilescu 2010). Pollutants can be organic compounds that are not naturally found in the environment or inorganic compounds present at concentrations exceeding background levels, with heavy metals representing the latter ones (Hamers et al 2006;Boyd 2010;Sahli et al 2012;Rieuwerts 2017;Savorelli et al 2017;Masindi and Muedi 2018;Burgos-Aceves et al 2018;Capillo et al 2018). Indeed, unlike organic pollutants, heavy metals once introduced into the environment cannot be broken down by chemical or biological processes (Ayangbenro and Babalola 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Examples include bioassays conducted with bacteria 7-9 and micro-algae 10,11 or by test batteries incorporating biotests of different trophic levels. 12-15 To obtain preliminary insights on the potential ecotoxicity of previously untested Moselle river watershed (Lorraine Province, France) sediments, as well as to compare the testing capabilities and usefulness of small-scale bioassays presently applied in our laboratories for such assessments, sediment was collected at seven sites of interest. Herein, we thus report sediment toxicity results generated with four different test procedures comprising the well-standardized Microtox solid phase bacterial luminescence inhibition assay (MSPA), 16 the LuminoTox photosynthetic efficiency inhibition measuring system for liquids 17 and solids, 18 the Hydra attenuata solid phase ecotoxicity assay (newly developed and described herein), as well as the Chironomus riparius solid phase assay.…”
Section: Introductionmentioning
confidence: 99%